2017
DOI: 10.1037/pspp0000099
|View full text |Cite
|
Sign up to set email alerts
|

How distinctive are morningness and eveningness from the Big Five factors of personality? A meta-analytic investigation.

Abstract: This study explores relations between measures of individuals' circadian preferences and the Big Five. To this end, we compared a model of circadian preferences that acknowledges morningness (M) and eveningness (E) as separate dimensions to that of a model that places M and E on a single continuum (M-E). Analyses of 620 correlations from 44 independent samples (N = 16,647) revealed weak to modest relations between both dimensions of circadian preferences and the Big Five personality traits. The strongest obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 148 publications
(220 reference statements)
6
47
2
Order By: Relevance
“…Our tests had good test-retest consistency, but the lack of correlation with chronotype could have many reasons, including the validity of our tests as measures of putative personality traits. We note that a recent meta-analysis of the human literature on personality and chronotype revealed that conscientiousness is the only 1 of the 5 personality traits that correlates significantly with chronotype, with a modest r = 0.29 [90]. Although we found no significant correlation between chronotype and the 3 behavioral traits that we tested, we did find a marginal correlation between our estimates of openness and neuroticism (r = −0.25).…”
Section: Discussioncontrasting
confidence: 72%
“…Our tests had good test-retest consistency, but the lack of correlation with chronotype could have many reasons, including the validity of our tests as measures of putative personality traits. We note that a recent meta-analysis of the human literature on personality and chronotype revealed that conscientiousness is the only 1 of the 5 personality traits that correlates significantly with chronotype, with a modest r = 0.29 [90]. Although we found no significant correlation between chronotype and the 3 behavioral traits that we tested, we did find a marginal correlation between our estimates of openness and neuroticism (r = −0.25).…”
Section: Discussioncontrasting
confidence: 72%
“…The term ‘circadian typology’ is often used synonymously and shows the emphasis on the categorization of chronotypes in this research tradition (e.g. Adan et al., 2012; Lipnevich et al., 2017). In comparison, Roenneberg et al.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the morningness preference has been linked to personality. Higher values in this dimension indicate a preference for getting up and going to bed early, feeling fit in the morning, and achieving peak performance earlier in the day (Lipnevich et al., 2017). The most established findings in meta‐analyses are that conscientiousness and agreeableness are positively related to morningness (Tsaousis, 2010; Lipnevich et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations